2012
DOI: 10.26719/2012.18.11.1107
|View full text |Cite
|
Sign up to set email alerts
|

Lid surgery for trachomatous trichiasis is negatively associated with visual disabilities and visual impairment in Oman

Abstract: Oman is at the threshold of eliminating blinding trachoma. We conducted a community-based survey in 2009-10 to study the association of trachomatous trichiasis (TT) status with visual acuity and blindness among the Omani population aged 40+ years. A total of 8191 eyes were examined and participants' demographic data were collected. TT was absent in 7890 eyes but 227 of these eyes had had lid surgery for TT in the past. TT was detected in 301 eyes, for the first time in 154 eyes and following lid surgery in 147… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The study [39] with a decrease in visual acuity assessed the subjects from 3 to 4 years after surgery, when recurrence was likely. A recent study [40] in Oman, which is very close to achieving trachoma elimination, found that the rate of blindness decreased significantly in people who had previous lid surgery, but there was no significant difference in blindness and severe visual impairment rates among those with trichiasis and those without trichiasis.…”
Section: Surgical Treatment Of Trichiasismentioning
confidence: 99%
See 1 more Smart Citation
“…The study [39] with a decrease in visual acuity assessed the subjects from 3 to 4 years after surgery, when recurrence was likely. A recent study [40] in Oman, which is very close to achieving trachoma elimination, found that the rate of blindness decreased significantly in people who had previous lid surgery, but there was no significant difference in blindness and severe visual impairment rates among those with trichiasis and those without trichiasis.…”
Section: Surgical Treatment Of Trichiasismentioning
confidence: 99%
“…Considering that females are at higher risk and more vulnerable to infection, one would think that screening and treatment efforts would be more targeted towards the female population. This is the case in many programs, but the gender gap remains a problem in Oman, which may not successfully eliminate trachoma until coverage is more equal between men and women [40]. In underdeveloped communities of India, as many as one-third of women had trachoma symptoms, but only 40% received any treatment [112].…”
Section: The Overall Effectiveness Of Safementioning
confidence: 99%
“…Later, it was reported that the BLTR procedure significantly improved visual acuity [25]. Moreover, a report from Oman [26] indicates that the rate of blindness decreased significantly in people who underwent lid surgery. TT recurrence after surgery shows rates ranging between 7.4% at one year to 62% at three years [2527].…”
Section: Discussionmentioning
confidence: 99%